مسؤولية المقاول والمقاول الفرعي - محمد، خوله كاظم (جامعة بابل, 2021)
إن الالتزام الرئيس. الذي ينجم عن عقد المقاولة والواقع على عاتق المقاول هو انجاز العمل الذي تعهد القيام به، فالمقاول ملزم بان ينجز العمل طبقا للشروط والمواصفات المتفق عليها وكذلك طبقا للشروط التي تستلزمها أصول الصنعة وتقاليدها، وقد يقوم المقاول بالتعاقد من الباطن لغرض اتمام العمل مع عدة مقاولين من الباطن إذا كانت طبيعة العمل موضوع المقاولة تسمح بذلك وإذا كان موضوع العمل يتطلب تنفيذ العمل الاستعانة بمقاول أخر والعمل يعد منجزا من قبل المقاول رغم استعانة في انجاز العمل بمقاول أخر، فكل من هؤلاء يعد مقاولا في حدود الاعمال التي يقوم بها، ويكون ملتزما بالضمان الخاص في هذه الحدود فلا يكفي القول بوجود مقاولة من الباطن أن يبرم المقاول الاصلي عقد مقاولة فرعي. له بل لابد وأن يرتبط العقد الفرعي بالعقد الاصلي وذلك بأن يشترك المقاول من الباطن في تنفيذ العقد الاصلي كليا او جزئيا. فالعقد الاصلي والعقد اللاحق يفترضان ذاتية المحل ووحدته وأن المقاول من الباطن أو الفرعي يجب أن يقوم بعمل في الموقع يتدخل بمقتضاه في تنفيذ العقد الاصلي الامر الذي يجسد وحدة العمل إذ أن المقاولة من الباطن لا تعدو أن تكون فرعا من العقد الاصلي، أما بالنسبة إلى مدى ضمان المقاول من الباطن لعيوب البناء، ينتهي التزام المقاول من الباطن بالضمان بمجرد أن يتسلم المقاول الاصلي العمل تمكنه من فحصه وكشف ما به من عيوب فاذا ظهرت عيوب خفية بعد ذلك فلا يكون المقاول من الباطن مسؤولا في المدة التي يقضي بها العقد أو العرف. وعلى ذلك لا يكون المقاول من الباطن مسئولا مباشرة نحو رب العمل، بل يبقى مسؤولا نحو المقاول الاصلي. The principal obligation which is caused by contract and actually the responsibility of the contractor contract is to get the job done, who has vowed to do, Valmquaol binding to complete the work in accordance with the conditions and specifications agreed upon, as well as in accordance with the conditions Tstjobha workmanship origins and traditions, have the contractor subcontract for the purpose of completing the work with promised subcontractors if the nature of the work contract subject permit and if the subject of the work requires the implementation of the use of a contractor last and work is done by the contractor despite the use of the completion of the work to another contractor, each of these is a contractor in the work of the borders, and be committed Special security in this border is not enough to say the existence of a sub-contractor to conclude a contract Contractor original contractor fled Aa him but must sub-contract and that the contract is linked to the original so that the sub-contractor involved in the implementation of the original contract in whole or in part. The contract original and subsequent contract Resume shop assume, unity, and that the sub-contractor or sub should be doing on-site intervenes whereby in the implementation of the original contract, which embodies the unity of action as the subcontracting is only a branch of the original contract, as to the extent of ensuring sub-contractor for construction defects, the commitment of the contractor ends subcontractors security once he receives the Contractor original work enables him to study it and figuring out what its defects if hidden defects emerged then be subcontractor liable only during the period that requires the contract or custom. ually it does not be a sub-contractor directly responsible to the employer, but remains responsible towards the original contractor.
Keywords: القرارات القضائية -- المقاولات الفرعية -- القانون المدني العراقي -- عقود المقاولة